2007
DOI: 10.1111/j.1439-0442.2007.00895.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Features of Spermatozoa of Swamp Buffalo AI Bulls in Thailand

Abstract: The appearance and incidence of sperm abnormalities was studied in 115 ejaculates, collected periodically over 1 year covering all seasons from five mature, healthy swamp buffalo (Bubalus bubalis) bulls reared under tropical conditions and serving as the current source of semen for artificial insemination (AI) in Thailand. Light microscopy of stained smears was used to investigate sperm head shape morphology, while unstained wet smears were used to examine other sperm abnormalities. The most commonly found mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The higher mass activity in the age group of 3 to 4 years was probably due to higher sperm concentration and low sperm abnormalities, which is also stated by Dhami and Kodagali (1988). Similarly, Koonjaenak et al (2007) reported that age had significant effect on total sperm number per ejaculate and initial sperm motility. It should be noted that the effect of age of bull is also influenced by managemental conditions.…”
Section: Effect Of Bull and Ejaculatementioning
confidence: 95%
See 1 more Smart Citation
“…The higher mass activity in the age group of 3 to 4 years was probably due to higher sperm concentration and low sperm abnormalities, which is also stated by Dhami and Kodagali (1988). Similarly, Koonjaenak et al (2007) reported that age had significant effect on total sperm number per ejaculate and initial sperm motility. It should be noted that the effect of age of bull is also influenced by managemental conditions.…”
Section: Effect Of Bull and Ejaculatementioning
confidence: 95%
“…Information regarding the effect of season, period and age on semen characteristics is available in different breeds and species (Mandal et al 2000;Mathur et al 2002;Bhat et al 2004;Ghosh 2004;Bhoite et al 2005;Waltl et al 2006;Chauhan 2007;Helbig et al 2007;Koonjaenak et al 2007;Mandal et al 2010;Ahmad et al 2011). Further, reports are also available regarding effect of bull and ejaculate on semen characteristics (Ravimurgan et al 2003;Waltl et al 2006).…”
Section: Introductionmentioning
confidence: 90%
“…Semen quality of the collected ejaculate, including the ejaculate volume, sperm motility and proportions of morphologically and physiologically normal spermatozoa, determines the quality of the processed (often frozen) semen and, ultimately, the potential fertility level achieved when artificial insemination (AI) is used (Rodriguez‐Martinez, 2000). Buffalo semen has been studied for some variables such as semen volume, sperm concentration, motility, sperm viability and sperm morphology (Kushwaha et al., 1955; Kapoor, 1973; Jainudeen et al., 1982; Sukhato et al., 1988; Nordin et al., 1990; Pant et al., 2003; Koonjaenak et al., 2006, 2007 a,b), but few studies have focused on cryopreservation or AI results (Heuer et al., 1987; Rasul et al., 2001; Sukhato et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This is associated with increasing the size of the testicles, nutritional status, geographic locations, season of the year, method of semen collection, and handling of bulls during collection (Tegegn et al, 1992;Mirza andZahid, 2003 andHafez, 2013) Dhami and Kodagali (1988) explained that PM and TM increase with age up to 5 years and starts to decrease as the age increases above 5 years. This increase could be due to high sperm concentration low sperm abnormalities, and management conditions as stated by Koonjaenak et al, (2007). Moreover, the decrease in semen attributed due to increasing age maybe due to decreasing function of the post-testicular glands and decrease in epididymis function and a change in the function of sperm mitochondria which is very important for sperm, although motility decreases with age in bulls, still meets the minimum standard requirements for AI (Sloter et al, 2006).…”
Section: Discussionmentioning
confidence: 99%